Super-Twisting Sliding Mode Control Law Design for Attitude Tracking Task of a Spacecraft via Reaction Wheels. (16th March 2021) - Li, Yang-Rui; Peng, Chao-Chung
Abstract : The attitude control has been recognized as one of the most important research topics for spacecraft. If the desired attitude trajectory cannot be tracked precisely, it may cause mission failures. In the real space mission environment, the unknown external perturbations, for example, atmospheric drag and solar radiation, should be taken into consideration. Such external perturbations could deviate the precision of the spacecraft orientation and thereby lead to a mission failure. Therefore, in this paper, a quaternion-based super-twisting sliding mode robust control law for the spacecraft attitude tracking is developed. The finite time stability based on the formulation of the linear matrix inequality (LMI) is also provided. To avoid losing the control degree of freedom due to the certain actuator fault, a redundant reaction wheels configuration is adopted. The actuators distribution associated force distribution matrix (FDM) is analyzed in detail. Finally, the reference tangent-normal-binormal (TNB) command generation strategy is implemented for simulating the scenario of the space mission. Finally, the simulation results reveal that the spacecraft can achieve the desired attitude trajectory tracking demands in the presence of the time-varying external disturbances.